Newly created municipalities in the Vale do Jequitinhonha and promotion of citizenship: a comparative analysis of social welfare indicators (Revista Espinhaço, 2015)
During the 1990s were created in Brazil over a thousand municipalities; in Minas Gerais the number was over a hundred, and the Vale do Jequitinhonha was twenty-four. This emancipation outbreak reflects the greater autonomy guaranteed by the Constitution of 1988 that allowed the states of federataion to legislate about the subject. Against the advantages and disadvantages of emancipation, it was observed that, starting from 1990s decade, the new municipalities created had greater progress in social welfare indicators than other categories. At the end of the analysis period (2000-2010), it was found that the synthetic indicators practically equalized, which shows to have been a reduction of social inequalities among municipalities in the Vale do Jequitinhonha. The social dimensions that contributed to the social development of the new municipalities were: culture, leisure, welfare and education.